Hubungan Dukungan Keluarga Terhadap Perilaku Medication Adherence Pada Penderita TB di UPT Puskesmas Pekauman Kota Banjarmasin - Ani, Ni Kadek; Irawan, Angga; Arief Wicaksono, Muhammad (Journal of Nursing Invention, 2023)
Background: Pulmonary Tuberculosis (TB) is one of the infectious diseases caused by the Mycobacterium Tuberculosis bacteria. The impact of TB includes multiple drug-resistant TB due to incomplete treatment, damage to the brain, eye disorders, damage to bones and joints, and the worst consequence of TB is death. There is a need for family involvement as PMO (Patient Medical Observer) in TB patients to change Medication Adherence behavior during the treatment process to achieve recovery. Objective: Understanding the relationship between family support and Medication Adherence behavior in TB patients at the Pekauman Health Center in Banjarmasin City. Method: This research used a quantitative method with a cross-sectional approach, sampling was taken using purposive sampling technique with a sample size of 35 people. Data collection was done using a questionnaire and data analysis was conducted using univariate and bivariate analysis with the Spearman rank test. Result: The majority of TB patients at the Pekauman Health Center in Banjarmasin City have high family support, which is 21 people (60%), and good Medication Adherence behavior, which is 30 people (85.7%). The result of the Spearman rank test showed that the significant value (2-tailed) was p-value = 0.002 <0.05, where Ho was rejected and Ha was accepted, which means there is a relationship between family support and Medication Adherence behavior in TB patients at the Pekauman Health Center in Banjarmasin City. Conclusion: The conclusion is that TB patients who receive high family support can influence Medication Adherence behavior in TB patients.